Patrimonio Alimentario y Turismo Cultural del Cantón Biblián, provincia de Cañar - Sarmiento Sarmiento, Lady Isabel (2023)
Tourists, at the time of deciding a travel destination, are becoming more demanding which is why they look for diversified products and services that allow them to enter the history and culture, that is why the investigation is intended to determine if the food heritage has an influence in the tourism culture of canton Biblian. The investigation is of mixed and descriptive type, with documentary and field method, as for design it is non-experimental and transversal because the instruments of evaluation were applied in a determined time, same that was previously revised and validated by experts, as well as the reliability through the use of SPPS software version 23.0, from which were obtained tables and graphics for interpretation. With regard to population involved in the research, were the managers of the food and beverage establishments that are in the cadaster of GAD municipal, meanwhile for the other variable was taken to local settlers, tourists who visit the sanctuary of the Virgen del Rocio, and the touristic train. After performing the check of each one of the hypotheses a high result was obtained that the food beliefs influence in cultural tourism of Biblian. For this reason, the proposal for the creation of a cultural gastronomic route was established for the festivities of the Virgen del Rocio, with the purpose to make known to local, national, and foreign people the wonders you can find in the green canton, starting from the preparation of yesteryear to weaving on looms with alpaca wool. It turns out that the food and cultural heritage culture form part of the value added in the tourism offer, this is because they don’t just get to know cultural, and natural spaces, but your visit is also complemented with the tasting of food that is prepared in the canton.